PENGEMBANGAN APLIKASI SMARTPHONE UNTUK MOBILE LEARNING PADA MATAKULIAH DESAIN GRAFIS DI STKIP MUHAMMADIYAH MUARA BUNGO - Fauziah F; Muhammad Hakiki; Ari Fajar Wismoyo; Maest Pyu Amar Dievan Qiusta (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
Technological developments in the digital transformation era occur dynamically very quickly, in a short time. This certainly affects the world of education where a concept and mechanism for the learning process is needed that integrates technology with education. The occurrence of the Covid-19 pandemic has resulted in the integration of technology with the world of education being urgently needed. One form of integrating education with technology is by developing applications for Mobile Learning (M-Learning). The research was conducted using the Research and Development method with a 4-D (four-D) Model approach, which consisted of 4 stages, namely: define, design, develop, and disseminate. This study aims to produce a smartphone application for mobile learning in graphic design courses at STKIP Muhammadiyah Muara Bungo that is valid, practical and effective. Data analysis was carried out using descriptive analysis techniques by describing the results of the validity, practicality, and effectiveness tests. Based on the results of the study, the findings obtained: (1) The smartphone application for mobile learning that was developed was declared valid in the media and material aspects, (2) Based on direct observation, the responses and responses of the application users were stated to be practical, (3) The smartphone application for mobile learning after being carried out testing is declared effective in improving learning outcomes. So, it can be concluded that the smartphone application for mobile learning in the graphic design course at STKIP Muhammadiyah Muara Bungo is valid, practical, and effective.